2017
DOI: 10.1109/tit.2017.2678988
|View full text |Cite
|
Sign up to set email alerts
|

Finite-Length Linear Schemes for Joint Source-Channel Coding over Gaussian Broadcast Channels with Feedback

Abstract: Abstract-We study linear encoding for a pair of correlated Gaussian sources transmitted over a two-user Gaussian broadcast channel in the presence of unit-delay noiseless feedback, abbreviated as the GBCF. Each pair of source samples is transmitted using a linear transmission scheme in a finite number of channel uses. We investigate three linear transmission schemes: A scheme based on the Ozarow-Leung (OL) code, a scheme based on the linear quadratic Gaussian (LQG) code of Ardestanizadeh et al., and a novel sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 43 publications
(141 reference statements)
1
20
0
Order By: Relevance
“…We note that linear and uncoded transmission, as implemented in the OL and in the LQG schemes, has important advantages, including low computational complexity, short coding delays and small storage requirements, which make this type of coding very desirable. We further note that although the LQG channel coding scheme of [32] for the two-user GBCF (with two messages) achieves the largest rate region out of all known channel coding schemes, in [36], it was shown that when the time horizon is finite, JSCC based on the OL scheme can achieve MSE distortion pairs lower than the JSCC based on the LQG scheme. In the present work, we analyze lossy source coding over GBCFs using SSCC and JSCC schemes based on a different performance metric: the EDT.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…We note that linear and uncoded transmission, as implemented in the OL and in the LQG schemes, has important advantages, including low computational complexity, short coding delays and small storage requirements, which make this type of coding very desirable. We further note that although the LQG channel coding scheme of [32] for the two-user GBCF (with two messages) achieves the largest rate region out of all known channel coding schemes, in [36], it was shown that when the time horizon is finite, JSCC based on the OL scheme can achieve MSE distortion pairs lower than the JSCC based on the LQG scheme. In the present work, we analyze lossy source coding over GBCFs using SSCC and JSCC schemes based on a different performance metric: the EDT.…”
Section: Introductionmentioning
confidence: 87%
“…JSCC for the transmission of correlated Gaussian sources over GBCFs when the number of transmitted symbols is finite (referred to as the finite horizon regime) was previously considered in [36], which studied the minimal number of channel uses required to achieve a target MSE distortion pair. Three linear encoding schemes based on uncoded transmission were considered: the first scheme was a JSCC scheme based on the coding scheme of [28], to which we shall refer as the OL scheme; the second scheme was a JSCC scheme based on the scheme of [32], to which we shall refer as the LQG scheme; and the third scheme was a JSCC scheme whose parameters are obtained using dynamic programming (DP) (in the present work we discuss only the former OL and LQG schemes since the scheme based on DP becomes analytically and computationally infeasible as the number of channel uses goes to infinity).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4] we adapted the LQG scheme for [11] to the transmission of correlated Gaussian sources over GBCFs. We have observed in [12] that obtaining a closed-form expression for E LQG (D) seems intractable. Yet, using the results and analysis of [12] one can find good approximations for E LQG (D).…”
Section: An Upper Bound On E(d) Via Jsccmentioning
confidence: 99%
“…Previous works on GBCFs mainly studied the channel coding aspects which applies to independent and uniformly distributed messages [9]- [11]. JSCC of correlated Gaussian sources over GBCFs was also studied in [12], in which the minimal number of channel uses required to achieve a target MSE distortion pair was characterized for three linear encoding schemes, using uncoded transmission: The first scheme is a JSCC scheme based on the coding scheme of Ozarow and Leung [9], to which we shall refer as the OL scheme; the second scheme iss a JSCC scheme based on the linear quadratic Gaussian (LQG) coding scheme of [11], to which we shall refer as the LQG scheme; and the third scheme iss a JSCC scheme whose parameters are obtained using dynamic programming (DP). 1 We note that the advantages of linear and uncoded transmission, as implemented in the OL and LQG schemes, include a low computational complexity, low coding delays, and low storage requirements.…”
Section: Introductionmentioning
confidence: 99%